ANEMIA EDUCATION AND CONSUMPTION OF BLOOD SUPPLY TABLETS, ANEMIA PREVENTION BEHAVIOR IN ADOLESCENT FEMALES; LITERATURE REVIEW - Kadek Primadewi (Jurnal Medicare, 2025)
Background: Nutritional anemia caused by iron deficiency is called iron deficiency anemia. The prevalence of anemia is 27.2% suffered by women, lack of awareness of the consequences of anemia and resistance among adolescents to consume iron tablets regularly. Compliance of adolescent girls in consuming blood supplements is an important factor in increasing hemoglobin levels and preventing anemia Objective: To determine the behavior of preventing anemia with education and consumption of iron tablets in adolescent girls based on literature studies. Method: This study uses a literature review with the Prisma method as data collection by searching for journals or articles through Google Scholar, 5 main journals were used to be reviewed and analyzed. Results: There is a significant relationship between knowledge, attitudes, and practices with compliance. The better the knowledge, attitudes and practices, the higher the compliance of drinking iron as an effort to prevent low hemoglobin levels or anemia. Conclusion: There is a relationship between education and consumption of iron tablets as an effort to prevent anemia in adolescent girls.